Mental Health, Suicidality, Health, and Social Indicators Among College Students Across Nine States in India - Anish V. Cherian; Gregory Armstrong; H. Sobhana; Tilahun Haregu; Sonia P. Deuri; Shrinivasa U. Bhat; Agnieta Aiman; Vikas Menon; Anil V. Cherian; Yamini Kannappan; Tinu Thamby; Soyuz John; et al. (Indian Journal of Psychological Medicine)
Background: The prevalence of mental health issues among youth is significantly high globally. This article presents findings from a survey that examined psychological distress, suicidal thoughts and behaviors, and health and social indicators among college students in India. Methods: The study recruited 8,542 students from 30 universities spanning nine Indian states, utilizing a questionnaire that included the Patient Health Questionnaire-9 (PHQ-9) and Generalized Anxiety Disorder-7 (GAD-7) to measure depression and anxiety symptoms. It also examined the prevalence of suicidal thoughts, attempts, non-suicidal self-injury, and other health and social factors. Results: Findings indicate that 18.8% and 12.4% of students had considered suicide over their lifetime and in the past year, respectively, with 6.7% having attempted it at some point in their lives. Among those with lifetime suicidal thoughts, more than one-third (38.1%) reported having previously disclosed these thoughts to someone, with friends being the most common confidants. Furthermore, one-third (33.6%) of participants reported moderate to severe symptoms of depression, and one-quarter (23.2%) reported moderate to severe symptoms of anxiety. Conclusions: The study revealed a significant prevalence of depressive and anxiety symptoms, as well as suicidal thoughts and attempts among college students in India. The study underscores the critical need for interventions aimed at improving mental health and supporting this demographic.